Recommending Physical Activity During the COVID-19 Health Crisis. Fitness Influencers on Instagram - Godefroy, Joseph (Frontiers in Sports and Active Living, 2020)
This study aims to show how fitness content creators on Instagram used the COVID-19 lockdown period to massively recommend physical activity to their followers. The individuals in question were not professional fitness trainers. Rather, their Instagram activity consisted in sharing images that were more about the staging of their bodies than about educational content. But given the closure of fitness clubs, these influencers changed the images they shared daily towards a massive dissemination of fitness training to be done at home. At the same time, we will look at the case of a chain of fitness clubs that, in order to manage the repercussions of the forced closure of its establishments, offered live fitness sessions online via its Instagram account. This article reports on the consequences related to the shutdown of the fitness training industry in France and questions the new dynamic of online fitness recommendations that was observed during the COVID-19 pandemic.